Continuing The Legacy: An Update On The Construction Of The New Second Avenue Subway - Jaidev Sankar (Society for Mining, Metallurgy & Exploration)
The dream of constructing the new Second Avenue Subway in New York has finally become reality as the first construction contract package is currently underway. This first contract requires the construction a TBM Launch Box in the middle of Second Avenue from which a Tunnel Boring Machine (TBM) will bore two tunnels south to 63rd Street. This paper will discuss the design of this contract and how construction has progressed including preparation, site constraints, utility construction and com-munity impacts while highlighting the challenges of working in an urban environment. It will also discuss moving forward on this major project outlining the remaining contract packages including their scope and status.